2020
DOI: 10.1007/s11356-020-10540-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymer types ingested by northern fulmars (Fulmarus glacialis) and southern hemisphere relatives

Abstract: Although ingestion of plastic by tubenosed seabirds has been documented regularly, identification of the polymer composition of these plastics has rarely been described. Polymer assessment may assist in identifying sources and may indicate risks from additives occurring in specific types of polymers. Using known test materials, two identification methods Fourier transform infrared spectroscopy and near infrared spectroscopy (FTIR and NIR) were compared. Although both methods were found to be similarly suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 72 publications
(91 reference statements)
0
10
0
2
Order By: Relevance
“…The percentage of industrial plastics within this sample set (mean = 9%) was equal to or lower than the percentage of industrial plastics reported in previous studies in seabirds and specifically Great Shearwaters (Figure 2; Moser and Lee, 1992;Ryan, 2008;Bond et al, 2014;Van Franeker and Law, 2015;Avery-Gomm et al, 2017;Kühn et al, 2020). The reduced incidence of industrial plastics is likely related to decrease of industrial pellets in marine environments due to source reduction efforts over time (Van Franeker and Law, 2015).…”
Section: Industrial Plastics Generally Remain a Minor Component Of Ingested Plastic Loadsmentioning
confidence: 46%
“…The percentage of industrial plastics within this sample set (mean = 9%) was equal to or lower than the percentage of industrial plastics reported in previous studies in seabirds and specifically Great Shearwaters (Figure 2; Moser and Lee, 1992;Ryan, 2008;Bond et al, 2014;Van Franeker and Law, 2015;Avery-Gomm et al, 2017;Kühn et al, 2020). The reduced incidence of industrial plastics is likely related to decrease of industrial pellets in marine environments due to source reduction efforts over time (Van Franeker and Law, 2015).…”
Section: Industrial Plastics Generally Remain a Minor Component Of Ingested Plastic Loadsmentioning
confidence: 46%
“…conteúdo gastrointestinal Mallory et al, 2008;Colabuono et al, 2009;Tourinho et al, 2010;Gray et al, 2012;Codina-Garcia et al, 2013;Bond et al, 2014;Jimenez et al, 2015;Acampora et al, 2016;Herzke et al, 2016;Poon et al, 2017;Petry & Benemann, 2017;Ryan, 2008Ryan, , 2016Roman et al, 2016Roman et al, , 2019Hyrenbach et al, 2017;Provencher et al, 2009, 2014, 2018b, van Franeker et al, 2011Tavares et al, 2017;Avery-Gomm et al, 2018;Lavers et al, 2019;Avery-Gomm, 2020;Baak et al, 2020;Padula et al, 2020;Kühn, 2020;Bourdages et al, 2021;Hamilton et al, 2021;Kühn et al, 2021. DOI: 10.37002/biobrasil.v11i3.1829 Métodos para Avaliação da Exposição a Poluentes Plásticos em Procellariiformes: Revisão e Padronização de Protocolos…”
Section: Aves Mortasunclassified
“…conteúdo gastrointestinal Mallory et al, 2008;Provencher et al, 2009;Gray et al, 2012;Codina-Garcia et al, 2013;Bond et al, 2014;Acampora et al, 2016;Avery-Gomm et al, 2016Tavares et al, 2017;Baak et al, 2020;Yorio et al, 2020;Kühn, 2020;Bourdages et al, 2021;Hamilton et al, 2021;Kühn et al, 2021. Lusher et al, 2015, 2018.…”
Section: Aves Mortasunclassified
“…Although no data on the occurrence of industrial plastics in glaucous gulls are available, a study by Seif et al (2018) examined 284 pieces of debris in other gulls and found only one single industrial pellet. The investigation of plastic in seabirds since the 1980s has shown a change in the global plastic composition where industrial plastic is declining, and user plastics dominate (Ryan, 2008;Ask et al, 2020;Kühn et al, 2021).…”
Section: Plastic Occurrencementioning
confidence: 99%